(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acute pancreatitis (AP) is a multifactorial inflammatory disease of the pancreas characterized by premature activation of digestive enzymes, acinar cell injury, and systemic inflammation. The pathogenesis of AP is tightly linked to the activation of key inflammatory signaling pathways and mediators that orchestrate the immune response.